2010
DOI: 10.5138/ijdd.2010.0975.0215.02034
|View full text |Cite
|
Sign up to set email alerts
|

Formulation and evaluation of biodegradable microspheres of tinidazole.

Abstract: The aim of present study is to develop biodegradable microspheres of Tinidazole. Bovine Serum Albumin was used for the preparation of microspheres. They were made in four batches. The emulsion cross-linking method was used for the preparation. The quantity of BSA varies for each formulation. Formulations were evaluated for particle size, Melting point, TLC, entrapment efficiency and in vitro release studies. Depending upon the drug to polymer ratio, the entrapment, loading were found to range between 48, 55, 7… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2013
2013
2022
2022

Publication Types

Select...
4
2

Relationship

0
6

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 5 publications
0
4
0
Order By: Relevance
“…Melting point determination was done by using melting point apparatus. Small amount of pure drug of Tolbutamide was taken in a capillary tube and it was kept in the melting point apparatus and the melting point was noted [19][20][21][22].…”
Section: B) Melting Pointmentioning
confidence: 99%
“…Melting point determination was done by using melting point apparatus. Small amount of pure drug of Tolbutamide was taken in a capillary tube and it was kept in the melting point apparatus and the melting point was noted [19][20][21][22].…”
Section: B) Melting Pointmentioning
confidence: 99%
“…Melting point determination was done by using melting point apparatus. Small amount of pure drug of Metformin HCl was taken in a capillary tube and it was kept in the melting point apparatus and the melting point was noted 10 .…”
Section: B) Melting Pointmentioning
confidence: 99%
“…Abdallah et al 19 found that, the mean diameter of the microspheres was increased significantly as the drug: polymer ratio was varied from 1:1 to 1:5. Low concentration of Eudragit RS100 resulted in a low viscosity of the polymer solution which in turn resulted in smaller emulsion droplets in the aqueous phase 20,21 . Also, from the same table, it can be also noticed that, the size range and mean diameter of the products prepared on using 50%, 66.66% or 80% theoretical drug content are nearly double to that prepared on using 20% or 33.33% theoretical drug content products which is in agreement with what stated before about there is a sharp cut in the frequency distribution curve between these products.…”
Section: Determination Of the Actual Drug Contentmentioning
confidence: 99%